2009
DOI: 10.1111/j.1528-1167.2009.02088.x
|View full text |Cite
|
Sign up to set email alerts
|

The antiepileptogenic effect of electrical stimulation at different low frequencies is accompanied with change in adenosine receptors gene expression in rats

Abstract: SUMMARYPurpose: Previous studies have shown that the anticonvulsant effects of low-frequency stimulation (LFS) can be affected by activation of adenosine receptors. In the present study, the effect of LFS at different frequencies on kindling rate and adenosine receptors gene expression was investigated. Methods: Animals were kindled by perforant path stimulation in a rapid kindling manner. LFS (0.5, 1, and 5 Hz) was applied after termination of each kindling stimulation. Seizure severity was measured according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…In conclusion, obtained results in combined with our previous experiments (Sadegh et al, 2007;Jahanshahi et al, 2009;Mohammad-Zadeh et al, 2009) show a possible role for G i/o protein activation in mediating the antiepileptogenic effects of LFS. We summarized this information in figure 6.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In conclusion, obtained results in combined with our previous experiments (Sadegh et al, 2007;Jahanshahi et al, 2009;Mohammad-Zadeh et al, 2009) show a possible role for G i/o protein activation in mediating the antiepileptogenic effects of LFS. We summarized this information in figure 6.…”
Section: Resultssupporting
confidence: 82%
“…Obtained results indicated that LFS administration could slow down the acquisition of perforant path rapid kindling seizures. Similar our previous reports (Mohammad-Zadeh et al, 2007;Jahanshahi et al, 2009;Mohammad-Zadeh et al, 2009), more stimulations were needed in animals that received LFS during kindling procedure to achieve higher seizure stages. In addition, their cumulative ADDs during 7 days of stimulations were lower than kindled animals.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, low or moderate Ado concentrations in the human cerebral cortex and hippocampus correlate well with the medium to high A 1 receptor expression in these brain regions [30,56] suggesting the involvement of Ado and its receptors in the modulation of hippocampal and cortical activity in pathological conditions such as epilepsy. It has also been supported by the demonstration of an epilepsy-induced decrease in A 1 receptor expression in chronic seizures [67,[158][159][160]228] and adaptive changes in Ado receptors after seizures [111]. Activation of A 2B receptors by elevated Ado levels may induce the release of proinflammatory interleukin-6 (IL-6) from astrocytes leading to increased expression of A 1 receptors and their functions in the brain [229,230], which may explain (i) the increase of A 1 receptor expression after seizures parallel with increasing Ado level and (ii) the higher level of IL-6 in the brain areas (e.g., in the hippocampus and cortex) of epileptic patients and rats [186,[231][232][233], which may have a protective effect against subsequent seizures [230].…”
Section: Adenosine Receptor Agonists and Antagonistsmentioning
confidence: 82%
“…The anticonvulsant effects of low-frequency stimulation have been correlated with changes in adenosine receptor expression [43], and vagal nerve stimulation has been associated with alterations in a variety of neurotransmitters and hormones in cerebrospinal fluid [44]. Furthermore, the progressive improvement in outcome associated with electrical stimulation for movement disorders [45] and epilepsy (see below) [23,46], suggest that synaptic, neurochemical, and/or expression changes are occurring in response to electrical stimulation of the pathologic neural network.…”
Section: Mechanism: Neuromodulation Via Electrical Stimulationmentioning
confidence: 99%